Pengaruh Kompensasi dan Lingkungan Kerja terhadap Turnover Intention Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Pancaran Energi Transportasi - Reza, Syah; Sitorus, Guston; Wijaya, Robby (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of compensation and work environment on turnover intention, with job satisfaction as an intervening variable, among drivers/helpers at PT. Pancaran Energy Transportasi. The research employs a quantitative approach with a population of 114 drivers/helpers in the company. The analysis method used is path analysis, utilizing a Likert scale in the questionnaire. The research results indicate that compensation and work environment have a positive and significant impact on job satisfaction. Compensation also has a positive and significant effect on turnover intention, while the work environment does not have a direct significant impact on turnover intention. Job satisfaction also does not have a direct significant impact on turnover intention. Furthermore, compensation and work environment directly and significantly influence turnover intention through job satisfaction.